Preceptorship of territory, new practices and knowledge in the strategy of continuing education in family health strategy: the case study of Sobral, Ceara, Brazil - Pagani, Rosani; Andrade, Luiz Odorico Monteiro de (Saúde e Sociedade, 2012)
This paper aims to present a new actor in the Health's Unique System of Brazil (SUS), the preceptor of territory, and discuss his performance. The implementation of Family Health Strategy (ESF) has led to intense discussion about the challenge of professional training to work in this model, in a process of continuing education in health. Sobral, city in Ceará (north-east of Brazil) has created, in 1999, a multi-professional residency program, and in it, the preceptorship of territory. In 2001, Sobral's City Hall received financial incentive of the provincial government and created the School of Family Health Visconde de Saboia where these programs of education are based. This study aimed to analyze the deployment and operation of territory preceptorship, describing the tutors' process of work, to understand their skills and to discuss the process of permanent-learning strategy developed at the Family Health's strategy in Sobral. We use a qualitative approach, the case study, with the following instruments: interviews, questionnaires and focal groups. Data were analyzed with the method of "Collective Subject Speech". Among the study's findings, the preceptor of the territory is identified as a professional who works directly with residents in the territories and displays a broad variety of competences, such as conceptual knowledge of the field of public health, human relations, problem based knowledge and methodologies of continuing education in health and community. He should also be able to establish relations of friendship, cooperation and participation. the debate is helping the definition of the role of the territory preceptor in Sobral within a function that is still being consolidated - that of an educator implied in the creation of SUS.